2015
DOI: 10.1021/nl503563g
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Resonances of Highly Doped Two-Dimensional MoS2

Abstract: The exhibition of plasmon resonances in two-dimensional (2D) semiconductor compounds is desirable for many applications. Here, by electrochemically intercalating lithium into 2D molybdenum disulfide (MoS2) nanoflakes, plasmon resonances in the visible and near UV wavelength ranges are achieved. These plasmon resonances are controlled by the high doping level of the nanoflakes after the intercalation, producing two distinct resonance peak areas based on the crystal arrangements. The system is also benchmarked f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 49 publications
3
135
0
Order By: Relevance
“…Sub‐band gap absorption can be originated from other effect such as sample impurities or scattering . Next we assign the visible‐NIR absorption peaks to LSPR by the strong dependence of plasmon resonance wavelength on the varied solvent medium.…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…Sub‐band gap absorption can be originated from other effect such as sample impurities or scattering . Next we assign the visible‐NIR absorption peaks to LSPR by the strong dependence of plasmon resonance wavelength on the varied solvent medium.…”
Section: Figurementioning
confidence: 82%
“…Therefore it can be concluded that the LSPR is easily influenced by the effective local medium index. In these cases, the obtained MoO 3− x nanodots dispersed in different solvent can be viewed as a molecule sensing system, and the LSPR properties can be effected by the affinity between MoO 3− x nanodots and solvent molecules, not only the refractive index as reported in the literature …”
Section: Figurementioning
confidence: 99%
“…Indeed, at zero temperature and in the absence of doping, graphene, MoS 2 , and BP do not support plasmons. However, these excitations are activated by introducing additional charge carriers, which can be done through chemical doping [12], molecular physisorption [13], and electrostatic gating [14,15]. The latter is useful for electrically controlling plasmons, relying, for example, on a bottom-gate configuration, as depicted in the upper inset of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated sheet resistances were on the order of 10 5 , 10 8 , and 10 9 Ω/sq for WO 3-x , WSe 2 , and WO 3 , respectively, in good agreement with the MIM results. The high local conductivity in the partially oxidized regions, as shown by both the MIM and transport data, could lead to other interesting phenomena such as the plasmonic resonance reported in TMDC materials [31].We now turn to the compositional analysis of oxidized WSe 2 using time-of-flight secondary ion mass spectroscopy (ToF-SIMS), a sample-destructive method that provides 3D elemental information of materials. Fig.…”
mentioning
confidence: 99%